Analisis Peningkatan PDRB Provinsi Daerah Istimewa Yogyakarta - Lusi (Politeknik Kutaraja, 2021)
This study aims to determine what factors affect the Gross Regional Domestic Product of the tourism sub-sector in the Province of D.I. Yogyakarta. In this study using the dependent variable and the independent variable. The dependent variable includes the tourism subsector's Gross Regional Domestic Product and the independent variables include the number of tourist visits, the number of hotels, the number of tourist objects and travel agents. This research uses quantitative methods, namely the emphasis on numerical and data analysis using statistical methods which provide an explanation of the relationship between the independent variable and the dependent variable. The results of this study indicate that the variables of the number of tourists, the number of hotels, and travel agents have a positive and significant effect on the Gross Regional Domestic Product of tourism.